2009
DOI: 10.2214/ajr.08.1647
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists' Performance and Their Enjoyment of Interpreting Screening Mammograms

Abstract: Objective-One might speculate that radiologists who enjoy mammography may exhibit better performance than radiologists who do not.Materials and Methods-One hundred thirty-one radiologists at three Breast Cancer Surveillance Consortium (BCSC) registries completed a survey about their characteristics, clinical practices, and attitudes related to screening mammography. Survey results were linked with BCSC performance data for 662,084 screening and 33,977 diagnostic mammograms. Using logistic regression, we modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Workforce shortages are a concern in the field of radiology, where nearly half of radiologists report that they do not enjoy interpreting screening mammograms. 22 Our study, however, suggests that a workforce shortage in breast pathology interpretation may not be problematic. One promising development is the rapid advancement in whole slide imaging digital technology 23 for primary diagnosis.…”
Section: Discussionmentioning
confidence: 63%
“…Workforce shortages are a concern in the field of radiology, where nearly half of radiologists report that they do not enjoy interpreting screening mammograms. 22 Our study, however, suggests that a workforce shortage in breast pathology interpretation may not be problematic. One promising development is the rapid advancement in whole slide imaging digital technology 23 for primary diagnosis.…”
Section: Discussionmentioning
confidence: 63%
“…In support of this hypothesis, Carney et al [22] observed that radiologists with a higher discomfort with uncertainty have a higher false-positive rate during the diagnostic mammogram interpretation. However, other American studies have investigated the variability in the performance between radiologists in relation to the level of uncertainty during the reading of screening mammograms [23], their perception of medical malpractice [24], and their enjoyment of interpretation of screening mammogram [25], but no statistically significant effects were observed. Moreover, Ong et al [26] conducted a study in 1992-1993 on the utilisation of the early rescreen or recall in the United Kingdom.…”
Section: Discussionmentioning
confidence: 97%
“…It is likely that indicators of caseload volume and training or experience have an impact on job satisfaction and diagnostic accuracy owing to the resulting increase in skill and confidence. Radiologists who reported higher confidence or less uncertainty in their mammographic assessments had higher positive predictive values for detecting cancer and lower recall rates, especially among low-volume readers [22][23][24]. The clinical experience level and training of dermatologists or dermatopathologists has also been shown to have an impact on diagnostic accuracy of malignant melanomas [4,25].…”
Section: Discussionmentioning
confidence: 99%